Equestrian Injury Presentations to a Regional Trauma Centre in Ireland. (3rd June 2018) - Abdulkarim, A.; Juhdi, A.; Coffey, P.; Edelson, Lily
Abstract : Background . The Irish Equestrian industry provides over 12, 500 full time job equivalents contributing in excess of €454 million to the Irish economy annually. For such an important industry there is a paucity of information relating to equestrian injuries. Aims . The aim of this study was to determine the demographics, characteristics, and outcomes of equestrian related injuries presenting to the emergency department of a regional trauma centre in Ireland over the course of one year. Methods . Retrospective analysis of all 30, 700 presentations to the emergency department (ED) of the Midland Regional Hospital (MRH) Tullamore in 2013 was performed to identify equestrian related presentations. Patient demographics, mechanism of injury, radiology results, management, and follow-up data were collected and analysed using Microsoft Excel software. Results . A total of 149 equestrian related presentations were identified during the study period. There were significantly more females involved in equestrian injuries than males (58% versus 42%). Falling from a horse contributed to significantly more presentations and admissions than any other cause. 36% of presentations were associated with a radiological abnormality. Types of injuries identified included skeletal fractures (27.5%), joint dislocation/subluxation (5%), concussion (12.5%), and splenic laceration/intraperitoneal haemorrhage (1%). Admission or transfer to tertiary care was required for 18% of equestrian injuries. Only 43% of presentations were discharged back to primary care from the emergency department. Conclusion . This study identifies a high incidence of morbidities associated with equestrian presentations. In addition we recognised populations at risk of specific injuries and described high-risk mechanisms of injury.